Hakikat Belajar dalam Istilah Ta'allama, Darasa, Thalaba, Perspektif Pendidikan Agama Islam - Harahap, Musaddad (Al-Hikmah: Jurnal Agama dan Ilmu Pengetahuan, 2019)
The current development of educational science has created many learning concepts. Some of Muslims has been ignored about these findings. One side deserves appreciation at the same time, but on the other side Muslims must directing their attention to study the concept of learning process in Islam itself. With the Literature Study or Library Research Method, learning process in Islam is a very important theme. The term learning process has been used in the sources of Islamic teachings (Al-Qur'an and Sunnah) there are at least three terms, namely ta'allama, darasa, and thalaba. From these three terms, it can be understand that learning process in Islam is an activity that is carried out seriously and need concentration, arising from a sincere intention, and carried out continuously. Learning process must also be pursued through the teacher, while a teacher should giving the attention to the readiness of students in receiving knowledge. Success or failure of learning process is largely determined by how physical and psychological involvement from the student as human being. The most important learning purpose according to the perspective of Islamic education is the practice of achieving the blessings from Allah swt.